UI/UX Design for the Mobile-Based Caktrip Application in the Tourism Sector in Surabaya - Prasasti Karunia Farista Ananto; Devina Nur Rahmadani S.P; Aurelia Salsabiila Putri; Melinda Citrasena Cahyaningrum; Bondan Setya Adi N (Jurnal Multidisiplin Sahombu, 2026)
The tourism sector in Surabaya has shown significant potential; however, information regarding tourist destinations remains fragmented, making it difficult for visitors to obtain accurate data related to locations, ticket prices, facilities, and parking availability. This study aims to design the UI/UX of the CakTrip mobile-based tourism application as a solution to provide integrated destination information and streamline the ticket-booking process. The Design Thinking method was employed, consisting of the Empathize, Define, Ideate, Prototype, and Testing stages. In the Empathize stage, findings revealed that users experience difficulties in accessing clear and centralized tourism information. The Define stage resulted in a problem formulation emphasizing the need for more comprehensive and structured information. During the Ideate stage, various alternative solutions and user flows were developed to support easier navigation. Subsequently, the application prototype was created using Figma to visualize core features such as destination search, location details, ticket booking, and parking slot availability. The Testing stage was conducted to evaluate usability and ensure that the proposed design aligns with user needs. The results indicate that the Design Thinking approach is effective in producing an informative and user-friendly interface that enhances the overall experience of tourists planning their activities in Surabaya.